PENYULUHAN TENTANG BAHAYA NARKOBA DAN KENAKALAN REMAJA DALAM RANGKA PENINGKATAN PENGETAHUAN SISWA DI SMP 1 ANGKOLA BARAT - Siregar, Marniatun; Nur, Muhammad; nisyah, Khairun; Nikayanti, Ria; Ritonga, Siti Meiranda Hafsari; Ardina, Lili; Delima, Mas; Natunnah, Sofiyah; Halawa, Sirina; Nasution, Mutiah Dina; Parlindungan, Muhammad Thohir; Harahap, Raja MP; Nasution, Nurul Hidayah; Harahap, Olivia Feby Mon (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2022)
ABSTRACT Narcotics are natural, synthetic and semi-synthetic substances or drugs which can cause a decrease in consciousness, hallucinations and excitability in humans. According to Law no. 39 of 2009 concerning Narcotics states that narcotics are artificial substances or even those derived from plants that have hallucinatory effects, decrease consciousness, and cause addiction. These drugs can be addictive if used excessively. Utilization of these substances is as a painkiller and provide peace. Its misuse can be subject to legal sanctions. Youth is the future asset of a nation. But nowadays a lot is happening to teenagers, such as drugs and juvenile delinquency such as motorcycle gangs. Therefore, knowledge about drugs and juvenile delinquency is very important as a strategy in reducing things that can harm the future of adolescents. This community service aims to increase students' knowledge about drugs and juvenile delinquency. This community service activity was attended by 30 class IX students. This activity was carried out by delivering counseling materials about drugs and juvenile delinquency at SMP Negeri 1 Angkola Barat. This activity was also interspersed with discussions and questions and answers. The results of this community service activity were received enthusiastically by students. All activity participants stated that this community service was very useful because it could add insight into knowledge about drugs and juvenile delinquency which affect habits in everyday life. Keywords: teens, drugs, delinquency, teenagers